2022
DOI: 10.14639/0392-100x-n1775
|View full text |Cite
|
Sign up to set email alerts
|

Benign paroxysmal positional vertigo: is hypothyroidism a risk factor for recurrence?

Abstract: Objective. To investigate the relationship between risk of Benign Paroxysmal Positional Vertigo (BPPV) recurrence and hypothyroidism treated with hormone replacement therapy (HRT). Methods. 797 patients with idiopathic BPPV were divided into two groups: 250 patients with recurrence of BPPV (R-BPPV) and 547 patients without recurrence (NR-BPPV). Regarding patients with thyroid disease on HRT, we collected serum test results of thyroidstimulating hormone (TSH), free triiodothyronine f-T3, free thyroxine f-T4, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, in 2022, Hu et al [23] suggested that hypothyroidism is a risk factor for Menière's disease. Likewise, Tricarico et al [27] speculated that patients with hypothyroidism have an increased risk of recurrent BPPV, which is particularly high in hypothyroid patients with positive thyroid antibodies, suggesting an association between autoimmunity and recurrent vertigo. In addition, our observation is similar to the study by Hsu et al [38], who demonstrated a relationship between hypothyroidism and tinnitus, another symptom encountered in vestibular pathologies such as Menière's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2022, Hu et al [23] suggested that hypothyroidism is a risk factor for Menière's disease. Likewise, Tricarico et al [27] speculated that patients with hypothyroidism have an increased risk of recurrent BPPV, which is particularly high in hypothyroid patients with positive thyroid antibodies, suggesting an association between autoimmunity and recurrent vertigo. In addition, our observation is similar to the study by Hsu et al [38], who demonstrated a relationship between hypothyroidism and tinnitus, another symptom encountered in vestibular pathologies such as Menière's disease.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 131 articles were initially identified. After excluding duplicates, thyroid autoimmune diseases, and articles unrelated to the subject, 20 articles were retained [2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], providing access to the full text. The stages in the data collection process are described in Figure 1.…”
Section: Collection Of Bibliographical Datamentioning
confidence: 99%
“…Recently, the association between hypothyroidism and BPPV has been investigated 43 , 44 . Another study demonstrated that patients with hypothyroidism treated with hormone replacement therapy have an increased risk of BPPV recurrence, which is particularly strong for patients with Hashimoto’s thyroiditis and positive thyroid antibodies, suggesting an association between autoimmunity and recurrent BPPV, and thus the importance of investigating thyroid dysfunction 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, attention should be given to the multi-morbidity accompanying people with hypothyroidism, which most often results from chronic autoimmune inflammation of the thyroid gland [32]. Notably, in many papers, hypothyroidism itself is associated with dizziness, headache, de-pression, and arthritis, which can affect one's quality of life [57][58][59][60]. Moreover, COVID-19 infection, which has affected many individuals, can result in metabolic disorders and thyroid dysfunction, including hypothyroidism and subclinical hypothyroidism, thereby exacerbating low quality of life [61].…”
Section: Discussionmentioning
confidence: 99%